Alternative to Oil and Gas: Review of Economic Benefits and Potential of Wind Power in Pakistan. (29th November 2020) - Hu, Xinting; Imran, Muhammad; Wu, Mengyun; Moon, Hee Cheol; Liu, Xiaochen
Abstract : Pakistan is one of those countries that are heavily dependent on hydrocarbon fuel for energy production. This results in severe CO2 emissions that lead to climate change. Although renewable energy resources such as wind are available in abundance, they have not been fully utilized and so energy crises in Pakistan increase every year. This study focuses on using wind energy as an alternative to thermal power sources as the main source of power generation in Pakistan. This research also helps in designing a project management tool to prioritize sources of power generation, including both renewables and nonrenewables, while also considering projects' technical, environmental, social and economic criteria. An Analytical Hierarchy Process has been used to analyze the four main criteria and 12 subcriteria. The analysis revealed that wind energy is the best source among all options for power generation source, followed by solar. Oil, gas, and coal, the other three alternatives, were well below in a comparative analysis. Gas achieves overall better performance if only economic criteria are considered, but due to shortfalls in availability and diminishing reserves, this source is also not feasible. Relying on wind power as the only energy source will not be technically possible, but it can become a leading energy source inside Pakistan. This will reduce the burden on thermal energy sources and make the country more energy-secure, rather than relying heavily on imported oil and gas, as it currently does. Wind power generation capacity in Pakistan is increasing, so that the cumulative capacity is around 2118 MW installed and commissioned by the end of 2018.